EXECUÇÃO E ESTRATÉGIAS PARA MITIGAÇÃO DE ATAQUES DE NEGAÇÃO DE SERVIÇO EM SERVIDORES WEB: UM RELATO DE EXPERIÊNCIA - Ladeira, Ricardo de la Rocha; Instituto Federal Catarinense (2019)
This paper describes the execution of denial of service attacks performed on web servers configured with different Apache versions, trying to reflect scenarios commonly found in Federal Institutions of Higher Education in Brazil. The approach consisted of the following steps: (i) tool selection for the experiment; (ii) definition of attack parameters; (iii) execution of attack with a selected tool in (i) on servers with similar characteristics to those in production; and (iv) execution of an attack with changes in the firewall as a strategy to mitigate the attack. Based on the observed result, the default configuration does not protect servers from simple denial of service attacks, but the settings implemented in (iv) were sufficient to prevent similar attacks from being successful in future executions.